Indirect quantum sensors: improving the sensitivity in characterizing very weakly coupled spins. (29th September 2015) - Greiner, Johannes N.; Rao, D. D. Bhaktavatsala; Neumann, Philipp; Wrachtrup, Jörg
Abstract : We propose a scheme to increase the sensitivity and thus the detection volume of nanoscale single molecule magnetic resonance imaging. The proposal aims to surpass the T 1 limited detection of the sensor by taking advantage of a long-lived ancillary nuclear spin to which the sensor is coupled. We show how this nuclear spin takes over the role of the sensor spin, keeping the characteristic time-scales of detection on the same order but with a longer life-time allowing it to detect a larger volume of the sample, which is not possible by the sensor alone.